Chester Step Test in patients with cardiovascular disease: practical applications in a cardiovascular prevention and rehabilitation setting. (2nd January 2020) - Grove, Tim
Abstract: The Chester Step Test is a low-cost, sub-maximal exercise test, which is commonly used in the assessment of cardiorespiratory fitness in a cardiovascular prevention and rehabilitation setting. This review discusses the practical applications of the Chester Step Test in the context of its validity, reliability and predictability in measuring cardiorespiratory fitness. The Chester Step Test has been compared to the 'gold standard' treadmill test for validity. There was a strong correlation ( r =0.92) between predicted VO2 values in the test and actual measurements from the treadmill test. In addition, the Chester Step Test has good reliability, which eliminates the need for a practice test. Furthermore, the Chester Step Test can provide valuable information on the patient's exercise tolerance to specific levels of sub-maximal stress, risk stratification, and physical activity/exercise prescription.